Guidance coordinators tasks relationships as inferred from their functions and activities - Jeves, Dominga (Neri) 1940- ([Quezon City s.n.], 1972)
This study looked into the task relationships of guidance coordinators in the Division of Tarlac (school year 1970-1971). It was found that the task relationships may be inferred from the functions and activities of the guidance coordinators in the form of organizing and administering functions as per division memoranda, implementing the memoranda and conducting in-service training for the division, district and school levels.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Personnel service in education -- Tarlac (Province).